100 questions & answers about peripheral artery disease (PAD) - Mohler, Emile R.; Hirsch, Alan T. (Alan Tick) (Jones and Bartlett Publishers, 2010)
"What is Pad? What are the symptoms of PAD? Is there a cure for PAD? When might I need an angioplasty? How do I gain control over my life now that I have PAD?" -- Cover, p.1
Includes index
Keywords: Arterial Occlusive Diseases -- Popular Works; Peripheral vascular diseases -- Miscellanea; Peripheral Vascular Diseases -- Popular Works